USING THE BLUE OCEAN STRATEGY BY UKRAINIAN CINEMA NETWORKS IN UNCERTAIN ENVIRONMENT - Bozhena Sheremeta; Natalia Chukhrai (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the article is ukrainian film distribution market. In today's world, the movie rental market is a sector of the economy that has recently shown a trend of stable growth. This process in most European countries is associated with the introduction of the latest digital cinema technology, increasing the level of wealth of the population and the high popularity of multi-screen cinemas. Film distribution is a mechanism to support the development, promotion of national cinema, one of the main forms of leisure and intercultural dialogue. The goal of the article is to determine the feasibility of applying the blue ocean strategy by Ukrainian cinema networks to support the trend of dynamic development of the industry. After all, an effective concept of management in uncertain conditions can be a strategy of "blue ocean", the principles of which are considered in the article on the example of market participants in market cinemas of Ukraine. The following tasks were solved: construction of a new strategic canvas for state cinemas of Ukraine; search for new value for cinema visitors; analysis of the foreign market of cinemas. The following methods used are: methods of analysis and synthesis, systemic, structural method in the article were summarized approaches to choosing a methodology for strategic enterprise management, taking into account the contemporary challenges of economic change in the world. The following results were obtained – the directions and possibilities of application of the "blue ocean" strategy by Ukrainian cinema networks as a tool of strategic success in the field of cinema were developed; the paper proposes a new strategic outline of cinema networks of Ukraine on the basis of a survey of 160 cinema spectators; а strategic plan for state and municipal cinemas has been developed, based on an updated four-action model; benchmarking of the world's leading cinemas was conducted, on the basis of which practical recommendations for the development of Ukrainian cinemas of various forms of ownership were formed; proposals for the creation of a "blue ocean" for companies engaged in the provision of services for the demonstration film products in Ukraine were presented. Conclusion: studies of the use of the "Blue Ocean" strategy have shown that this process is impossible without creating a new value for the consumer.